Doxorubicin pretreatment enhances FAPα/survivin co-targeting DNA vaccine anti-tumor activity primarily through decreasing peripheral MDSCs in the 4T1 murine breast cancer model. (1st January 2020) - Geng, Fei; Bao, Xin; Dong, Ling; Guo, Qian-Qian; Guo, Jie; Xie, Yu; Zhou, Yi; Yu, Bin; Wu, Hui; Wu, Jia-Xin; Zhang, Hai-Hong; Yu, Xiang-Hui; et al.
ABSTRACT: The tumor microenvironment (TME) provides necessary nutrition for tumor growth and recruits immunosuppressive factors including regulatory T cells and myeloid-derived suppressor cells (MDSCs) to inhibit the anti-tumor immune response induced by immunotherapy. As a main TME component, cancer associated fibroblasts (CAFs) can restrain T cell infiltration and activity through extracellular matrix remodeling. Vaccines targeting fibroblast-activating protein α (FAPα), which is mainly expressed on the CAF surface, can eliminate CAFs in tumors and regulate the TME, enhancing the potency of T cell-mediated anti-tumor effects. However, the anti-tumor effects were not fully realized as the tumor induces a large number of peripheral MDSCs during its growth, rendering the body of mice in an immunosuppressive state and preventing the vaccine from inducing effective anti-tumor immune responses. Here, we developed a dual-targeted DNA vaccine OsFS, targeting tumor matrix antigen FAPα and tumor cell antigen survivin simultaneously, exhibited enhanced antineoplastic effects in an established breast cancer model. Moreover, doxorubicin (Dox) pretreatment to remove the peripheral MDSCs induced to regulate the peripheral immune environment could further facilitate the anti-tumor activity of the vaccine. These results indicated that combination treatment of the tumor cells and the TME dual-targeting vaccine plus Dox could effectively realize the anti-tumor activity of the vaccine by decreasing immunosuppressive factors and inducing more tumor-infiltrating lymphocytes, which may offer important guidance for clinical research regarding the combination of the DNA vaccine with low-dose Dox.